Pelatihan Pemanfaatan Sampah Organik Di Lingkungan Pondok Pesantren Putri Assunniyyah Kencong Jember - Zahirah, Aishwarya Shafa; Rifqi, Niswah Khaliya; Putri, Annisa Ika; Fatmala, Rizqi Eka; Fadhilatuzzahro, Mutiara; Ramadhani, Zahidah; Ramadhani, Sabina Fitri; Rahman, Fazlul (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Waste management is one of the important aspects of environmental conservation efforts, organic waste refers to waste derived from natural materials that are easily decomposed, such as food waste and dry leaves. This waste has the potential to be processed into useful compost, which can improve soil quality and support agriculture and plant growth. The process involves the decomposition of organic matter by microorganisms, such as bacteria and fungi, which turn the waste into a nutrient-rich material. Organic waste that is not handled properly can have a negative impact on environmental hygiene. The training on the utilization of organic waste into compost fertilizer conducted at Pondok Pesantren Putri Assunniyyah Kencong, Jember aims to provide skills and knowledge on organic waste management in making compost fertilizer. The implementation of this work program has three stages of implementation, namely socialization, training, and mentoring to female santri. During the training, the female students learned how to identify and collect suitable organic materials, such as vegetable scraps, fruits, and dry leaves, as well as hands-on practice of making compost fertilizer that can be used for the boarding school's agricultural land located on the 5th floor. The results of this organic waste utilization training show that the students have more interest in sustainable outcomes and a significant increase in the students' understanding of organic waste management. Keywords: Waste Management, Organic Waste, Compost Fertilizer